THE PUBLIC ROLE OF GREEN PERFORMANCE AND COMPETITIVE ADVANTAGES ON SUSTAINABILITY: ANALYSIS OF THE IMPORTANCE OF GREEN ORGANIZATIONAL CULTURE AND GREEN INNOVATION IN COMPANIES - Tjatur Ermitajani Judi; Achluddin Ibnu Rochim; Arif Darmawan (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2022)
Due to globalization and rapid technological development, improving efficiencies in a production system and an environmental management system at the same time is critical to long-term sustainability. This study tried to examine the relationship between some Green Company Concepts such as Green Organizational Culture, Green Innovation, and Green Performances and Competitive Advantage, as well as Sustainable Performances. This study gathered the data from 101 companies that are working in different sectors such as food production, education, pharmacy, and others. This study uses a quantitative approach and regression in analyzing process. The results show that Green Organizational Culture has a significant positive impact on Green Innovation. Green Innovation also has a significant positive impact on both Green Performance and Competitive Advantage. This study also proves that both Green Performance and Competitive Advantage have a significant positive impact on Sustainable Performance. The conclusion, contribution, and limitations are also discussed.